Optimum fuzzy sliding mode control of fuel sloshing in a spacecraft using PSO algorithm. (February 2020) - Navabi, M.; Davoodi, A.; Reyhanoglu, M.
Abstract: This paper introduces an Optimal Fuzzy Sliding Mode (OFSM) controller for the control of fuel sloshing in a spacecraft during orbital maneuvers. In order to optimize controller's gains for minimizing control inputs, a Particle Swarm Optimization (PSO) algorithm is employed. A novel gain scheduling of the OFSM controller is developed for the coupled spacecraft-fuel system. Fuzzy gains are produced on-line based-on rules that utilize dynamic system variables and the sign of saturation function of sliding surfaces. The fuel slosh is modeled as a fixed spherical mass and two spherical pendulum masses moving in a spherical tank. Computer simulations illustrate the effectiveness of the proposed controller in maneuvering spacecraft while suppressing fuel sloshing. The performance of the OFSM controller is compared to that of the optimum State-Dependent Riccati Equation (SDRE) controller. Highlights: An Optimal Fuzzy Sliding Mode (OFSM) controller is designed for the control of fuel sloshing in 3D spacecraft maneuvers. A Particle Swarm Optimization (PSO) algorithm is employed to optimize control gains. The performance of the OFSM controller is compared to that of the optimum State-Dependent Riccati Equation (SDRE) controller.